Question
upstudy study bank question image url

Consider the quadratic equation shown below: \[ 2 x=x^{2}+11 \] Determine the coefficients \( a, b \), and \( c \) corresponding to the quadratic formula: \[ \begin{array}{l} a=1 \\ b=-2 \\ c=11 \end{array} \] Now enter those coefficients into the quadratic formula below: \[ x=\frac{-\square \pm \sqrt{(\square)^{2}-4 \cdot \square \cdot \square}}{2 \cdot \square} \]

Ask by Lane Little. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The coefficients are: - \( a = 1 \) - \( b = -2 \) - \( c = 11 \) Plugging these into the quadratic formula: \[ x = \frac{-(-2) \pm \sqrt{(-2)^2 - 4 \cdot 1 \cdot 11}}{2 \cdot 1} \]

Solution

To solve the quadratic equation \( 2x = x^2 + 11 \), we first need to rearrange it into the standard form \( ax^2 + bx + c = 0 \). 1. Rearranging the equation: \[ x^2 - 2x + 11 = 0 \] From this equation, we can identify the coefficients: - \( a = 1 \) - \( b = -2 \) - \( c = 11 \) Now, we can substitute these coefficients into the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] Substituting the values of \( a \), \( b \), and \( c \): \[ x = \frac{-(-2) \pm \sqrt{(-2)^2 - 4 \cdot 1 \cdot 11}}{2 \cdot 1} \] This simplifies to: \[ x = \frac{2 \pm \sqrt{4 - 44}}{2} \] \[ x = \frac{2 \pm \sqrt{-40}}{2} \] Since the discriminant (\( b^2 - 4ac \)) is negative, this indicates that the solutions will be complex numbers. Now, we can express the final form of the quadratic formula with the coefficients filled in: \[ x = \frac{-(-2) \pm \sqrt{(-2)^{2}-4 \cdot 1 \cdot 11}}{2 \cdot 1} \] Thus, the coefficients \( a, b, c \) are: - \( a = 1 \) - \( b = -2 \) - \( c = 11 \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

First, let's rearrange the given equation \(2x = x^2 + 11\) into standard form. By moving all terms to one side, we get: \[ x^2 - 2x + 11 = 0 \] From this, we see that the coefficients correspond to: \[ a = 1, \quad b = -2, \quad c = 11 \] Now, let's plug these coefficients into the quadratic formula: \[ x = \frac{-(-2) \pm \sqrt{(-2)^2 - 4 \cdot 1 \cdot 11}}{2 \cdot 1} \] This simplifies to: \[ x = \frac{2 \pm \sqrt{4 - 44}}{2} \] Oh, but wait—it looks like we’ve got a negative number under the square root, leading us to imaginary solutions! So be prepared for some fun with complex numbers! And voila! Now we can fill in the blanks of the quadratic formula provided: \[ x = \frac{-(-2) \pm \sqrt{(-2)^2 - 4 \cdot 1 \cdot 11}}{2 \cdot 1} \]

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy